A Comparative Analysis of the Performance and the Microbial Ecology of Biological Sulphate Reducing Reactor Systems - Hessler, Tomas (Centre for Bioprocess Engineering Research, 2020)
Acid rock drainage (ARD) is defined as acidic waste-water contaminated with sulphate and heavy metals which is generated through the oxidation of sulphidic ores in the presence of water and oxygen. Mining activities accelerate this process by bringing these ores to the surface where they are further crushed and, eventually end up in waste rock dumps and tailing impoundments where they continue to generate ARD into perpetuity. Active mining operations are mandated to prevent the discharge of ARD into the environment. This ARD is commonly remediated by expensive yet highly effective active treatment strategies such as high-density sludge processes and reverse osmosis. South Africa has an extensive history of gold and coal mining which has left abandoned mine workings with associated waste rock dumps throughout northern and eastern parts of the country. As many of these mines have long been abandoned, the responsibility to mitigate the environmental impact of the generated ARD lies solely with government. Although these diffuse sites often generate smaller volumes of less aggressive ARD compared to that generated through mine water rebound, the sheer number and the continual ARD generation from these sites is a severe threat to South Africa's already poor water security. Biological sulphate reduction (BSR) has long been considered an attractive option for the longterm remediation of these low-volume sources of ARD – but its implementation has shown mixed success. BSR is a process catalysed through the innate metabolism of sulphate-reducing bacteria (SRB) which coexist within complex microbial communities. SRB themselves are a highly diverse group of anaerobic microorganisms which use sulphate as a terminal electron acceptor. The sulphide and bicarbonate produced during BSR can be used to precipitate heavy metals and aid in the neutralisation of the ARD, respectively. The implementation of BSR is, therefore, a comprehensive remediation strategy for diffuse sources of ARD. The study of BSR, using various reactor configurations and operating conditions shows much promise. However, the microbial ecology of the complex communities within BSR systems, and their links to the performance of BSR processes, has received far less attention in published literature. This is not a result of underappreciation of the role microbial communities but rather a historical lack of tools, specifically high-throughput techniques, available to assess complex microbial consortia. It is asserted that the success of a sustainable BSR process developed for the long-term remediation of ARD requires an in-depth understanding the microbial communities associated with this process. The identification of the microorganisms which are key to the process, thosewhich threaten the stability of the community and the optimal growth conditions of these microorganisms, can be used to inform how these bioreactors are designed and operated. This study investigated the performance and microbial ecology of several continuous BSR reactors using culture-independent metagenomic sequencing approaches. The performance and microbial ecology of these reactors were evaluated at a range of hydraulic residence times (HRT) over the course of approximately 1000 days of continuous operation, from five- through to one-day(s). The tested reactor configurations included a continuous stirred tank reactor (CSTR), an up-flow anaerobic packed bed reactor (UAPBR) and a linear flow channel reactor (LFCR) that were each operated in duplicate and supplemented with either lactate or acetate as an electron donor. The different reactor configurations and supplied electron donors, as well as the varied applied HRT, generated a range of microenvironments which were hypothesised to lead to the divergence of the initial microbial community of the inoculum and generate numerous distinct microbial communities throughout and across the reactor systems. 16S rRNA gene amplicon sequencing was used to assess the microbial community structure of the numerous populations across the reactor systems and monitor how these communities responded to the change in the applied HRT. Genome-resolved metagenomics was employed in parallel to recover the genomes of all predominant microorganisms identified through gene amplicon sequencing. This allowed the interrogation of the composition of the respective microbial communities as well as the genetic potential of each microorganism and encompassing the communities represented within specific reactor environments. The CSTRs were selected as these systems are characterised as well-mixed, support solely suspended biomass and kinetic equilibriums are achieved rapidly. This allows the performance of these reactors to be predictable and provides a benchmark to which the LFCRs and UAPBRs could be compared. The lactate-supplemented CSTR performed largely as anticipated based on available literature, demonstrating a maintained sulphate conversion of approximately 55% over the course of the study. The reactor achieved a maximum observed volumetric sulphate reduction rate (VSRR) of 17 mg/ℓ.h at a one-day HRT. The system supported a low SRB diversity, constituted almost entirely by a Desulfomicrobium and two Desulfovibrio operational taxonomic units (OTUs). The acetate-supplemented CSTR was able to maintain sulphate reducing performance at HRT where complete washout of SRB had been predicted based on literature. This reactor exhibited a maximum VSRR of 10.8 mg/ℓ.h at a 1.5-day HRT and was dominated by the same Desulfovibrio and Desulfomicrobium observed in the lactate-supplemented CSTR, along with several other SRB genera at lower abundance. The LFCRs demonstrated an approximately ten-fold greater biomass retention than the corresponding CSTRs. This was facilitated through the incorporation of carbon microfibres, whichfacilitated microbial colonisation and biofilm formation within the reactors. Surprisingly, the lactate-supplemented LFCR, underperformed compared to the lactate-supplemented CSTR, achieving a maximum VSRR of 14.8 mg/ℓ.h at a one-day HRT. This reduced performance, in spite of the enhanced biomass retention, was concluded to result from the out-competition of lactateoxidising SRB in the reactor by Veillonella and Enterobacter OTUs. The acetate-supplemented LFCR exhibited a period of underperformance before recovering and subsequently demonstrated a maximum VSRR of 17.1 mg/ℓ.h at a one-day HRT. Evaluations of the microbial communities of this system during the HRT study revealed a dramatic shift in the SRB communities from being dominated by Desulfatitalea and Desulfovibrio to being dominated predominantly by Desulfomicrobium and Desulfobacter. The UAPBRs are governed by plug-flow which resulted in the generation of gradients of decreasing substrates and increasing products throughout the height of the reactors. This, as hypothesised, resulted in the stratification of the microbial communities throughout the height of these reactors. This allowed many associations to be made between specific microorganisms and their ideal growth environments. Both UAPBRs demonstrated competitive sulphate reducing performance. The lactate-supplemented UAPBR proved especially successful as this system was able to maintain >95% sulphate conversion at one-day HRT, corresponding with a VSRR of 40.1 mg/ℓ.h. The performance of this reactor was attributed to the significant quantity of retained biomass and the successful harbouring of lactate-oxidising SRB towards the inlet zone of the reactor as well as propionate- and acetate-oxidising SRB towards the effluent zones of the reactor. The acetatesupplemented UAPBR exhibited a maximum VSRR of 23.2 mg/ℓ.h at a one-day HRT and a maximum sulphate conversion of 79% at a 2.3-day HRT. The stratification of the microbial communities within the acetate-supplemented UAPBR was less pronounced than the lactatesupplemented UAPBR, as a result of the fewer available volatile fatty acid species. However, the stratification which was observed in this system could be used to postulate the growth kinetics associated with the identified SRB – a Desulfobulbus was associated with rapid acetate oxidation in the inlet zone while a Desulfatitalea and a Desulfosarcina could be implicated in sulphate scavenging in the effluent zone of this reactor. This proved particularly valuable for elucidating the roles of these same SRB in the well-mixed reactor systems. Genome-resolved metagenomics was employed to recover the genomes of the microorganisms identified in these systems and determine the metabolic potential of these microorganisms. Hydrogen-evolving hydrogenase genes were found to be widespread in genomes not capable of sulphate reduction. In contrast, hydrogen-consuming hydrogenases as well as autotrophic gene pathways were common amongst SRB genomes. The ubiquity of hydrogenase genes in these environments indicated that inter-species hydrogen transfer was an important feature within thesemicrobial communities. The dual consumption of both acetate and hydrogen was concluded to have facilitated the maintained sulphate reducing performance of the acetate-supplemented reactor systems at short HRT where system failure had been predicted. Indices of replication (iRep) were used to estimate the instantaneous growth rates of the microorganisms from metagenomic shotgun sequencing datasets. This revealed that, at a four-day HRT, the microorganisms within the biofilms were comparably active to planktonic microorganisms. This, together with the dynamic changes in the composition of these biofilms during the HRT study, suggests these biofilms are even more active and competitive than previously thought. The combined use of next-generation gene amplicon sequencing and genome-resolved metagenomics has given unprecedented insights into the microbial communities of BSR reactor systems. Using this approach, it was possible to uncover a seldom discussed form of hydrogen cycling within BSR systems and has shown that there is no ‘one-size-fits-all' approach when inoculating BSR reactors. The SRB within these systems were often highly specialised to particular environments, specific electron donors and each showed differing growth kinetics. The success of long-term, semi-passive BSR reactor systems would benefit greatly from the tailoring of SRB inoculums informed by the chosen reactor configuration and operating conditions. The outcomes of the kinetic reactor experiments have led to several recommendations for the design and operation of these systems.